IN VITRO VIABILITY AFTER VITRIFICATION OF Mus domesticuts domesticus VLATOCYSTS CULTURED FROM ONE-CELL - BASILE, Leandro Francisco (Scientia Agraria, 2000)
Three experiments were carried out in order to evaluate the in vitro development of Mus domesticus domesticus (CF1xSWISS) blastocysts cultured from one-cell embryos after exposition and vitrification in a cryoprotectant solution composed of 9.0 M EG additioned or no of 0.3 M SAC. In the first experiment, after the culture of 755 one-cell embryos, were observed the hatching rates of 53.0% for HTF medium and 61.7% for KSOM medium (P>0,05) supplemented with 4 mg/ml BSA + 20 and 25 mM HEPES, respectively. In the second experiment were evaluated the capacity of the embryos to hatching after exposition to the cryoprotectant solutions proposed (VS1 = 1.8 M EG in PBS + 6% BSA (120 s) followed by 9.0 M EG in PBS + 6% BSA and VS2 = 9.0 M EG + 0.3 M SAC in PBS + 6% BSA). First the embryos were cultured from one-cell to blastocyst stage and after 152 blastocysts were exposed to the vitrification solutions (VS1 and VS2). The exposition dont showed significant difference (P>0.05) among the control (86.0%), VS1 (82.3%) and VS2 (78.4%) groups. In the third experiment 140 blastocysts cultured for 72 h in KSOM with 4 mg/ml BSA + 25 mM HEPES were vitrified in 0.25 ml modified straws (OPSm) in the cryoprotectant solutions previously described, reaching hatching rates of 45.7 an 41.4% in VS1 and VS2 (P>0.05), respectively. Then, it was concluded that both HTF and KSOM + BSA and HEPES produced a complete in vitro preimplantation embryos development. However, the embryos cultured in KSOM medium showed a homogeneous growing curvature and higher hatching rates, which can be another alternative for culture of one-cell embryos. Equally, there were no differences (P>0.05) in the hatching rates between Mus domesticus domesticus vitrified blastocysts in cryoprotectant solutions containing 9.0 m EG with or without the addition of 0.3 M SAC.